Design of Baudrate Adaptive RS485 Isolating Repeater - YANG Sheng-yua (Gong-kuang zidonghua, 2012)
For the problem that traditional RS485 isolating repeater needs waiting time for state conversion of sending and receiving, the paper proposed a design scheme of baudrate adaptive RS485 isolating repeater with programmable counter array of single-chip microcomputer as control core. It analyzed design principles and disadvantages of three kinds of traditional RS485 isolating repeaters, and introduced principle, calculation of baudrate and actual byte sending time of the baudrate adaptive RS485 isolating repeater. The practical application shows that data transmission of the repeater is stable and reliable under the condition of communication baudrate less than 100 kbit/s and can meet requirements of remote communication of mine-used products.